30 dekabrya 1922 : da zdravstvuyet 1yy vsesoyuznyy s'yezd sovetov - Parmeev, B (Плакат СССР (Plakat), 1988)
Symbols of the Soviet Union; drawing of men and women representing different ethnicities and nationalities in the Soviet Union Original title: 30 декабря 1922 : да здравствует 1ый всесоюзный съеза советов Suggested translation: 30 December, 1922. Long live the first all-Union congress of Soviets PO-1701